Oil Prices and the Stock Market - Ready, Robert C (Review of Finance, 2018)
Abstract This paper develops a novel method for classifying oil price changes as supply or demand driven using information in asset prices. Motivated by a simple model, demand shocks are identified as returns to an index of oil producing firms which are orthogonal to unexpected changes in the VIX index, with supply shocks capturing the remaining variation in oil prices. Demand shocks are strongly positively correlated with market returns and economic output, whereas supply shocks have a strong negative correlation. The negative correlation of supply shocks and returns is strongest in industries that produce consumer goods, while the positive correlation of demand shocks is stronger for industries which use relatively large amounts of oil as an input.